In Silico Study of Haematococcus pluvialis Biomarker Compound as Supplement to Fish Bone Remodelling - Daniar Kusumawati; Sri Widyarti; Maftuch Maftuch; Sri Rahayu (HAYATI Journal of Biosciences, 2022)
This study aims to determine the docking predictions for RAR, RXR, and ROR in the bone remodeling pathway using Haematococcus, which is the highest carotenoid-producing microalgae. Furthermore, it determines the projection of using this carotenoid-producing alga in bone development. Carotenoids include provitamin A and non-provitamin A, which are predicted to replace vitamin A in bone control. It is also required in silico proof of carotenoids' function of bone remodeling control. Furthermore, molecular and visualization docking validation was conducted using PyRx and Discovery Studio Visualizer software respectively. According to binding affinity and RMSD value, each biomarker compound had particular binding sites on RARα, RARβ, RORβ, and RORγ. Astaxanthin was the only compound with binding sites on all four receptors. Through enzymatic action, provitamin A carotenoids can serve as a precursor to retinol, allowing them to act as a native RXR ligand. Therefore, the biomarker compound used in Haematococcus pluvialis can replace the role of vitamin A in the regulation of fish bones. The prediction of bone regulation in biomarker compounds through the RAR-RXR pathways inhibited osteoblast and osteclast. Otherwise, VDR-RXR pathways regulated osteoclast maturation and osteoblast mineralization.